LEGAL DIMENSIONS OF THERAPEUTIC COMMUNICATION IN MIDWIFERY CARE: PROTECTING PATIENT RIGHTS AND ENSURING PATIENT SAFETY IN INDONESIA - Dida Wanti; Rosmala Atina Rosadi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
Therapeutic communication is a fundamental component of quality midwifery care that extends beyond clinical interaction to encompass legal and ethical responsibilities. In Indonesia, the enactment of Law Number 17 of 2023 on Health has reinforced the protection of patient rights, informed consent, and patient safety, thereby increasing the legal significance of effective communication between midwives and patients. This study aims to examine the legal dimensions of therapeutic communication in midwifery care and its role in protecting patient rights while ensuring patient safety. Employing a normative legal research design, the study adopts statutory, conceptual, and comparative approaches to analyze relevant legislation, professional standards, ethical codes, and international guidelines concerning health communication and patient safety. The analysis demonstrates that therapeutic communication constitutes not only a professional competency but also a legal obligation that underpins informed consent, respect for patient autonomy, shared decision-making, and the prevention of medical disputes. Furthermore, effective communication strengthens patient trust, reduces the likelihood of adverse events, and enhances legal accountability in midwifery practice. The study proposes an integrated legal framework positioning therapeutic communication as a bridge between regulatory compliance and safe, patient-centered maternity care. Strengthening legal awareness and communication competence among midwives is therefore essential for improving healthcare quality and safeguarding both patients and healthcare professionals in Indonesia.